The assessment of cholinesterase from the brain of Anabas testudineus as detection of metal ions - Abdul Wahab Sha'arani, Shakirah (2015)
Anabas testudineus (A. testudineus) is a freshwater fish that belongs to the family of Anabantidae and its local name in Malaysia is ‘Ikan Puyu’. It can be used as a bioindicator for heavy metal contamination as it is quite sturdy and ideally suited for experimentation in laboratory for a longer period. The present study aimed to partially purify cholinesterase (ChE) from the brain extract of A. testudineus and to study the optimization of assay conditions and inhibition effect towards ChE. The result showed that ChE was successfully partially purified from the brain extract of A. testudineus using DEAE-cellulose through ion exchange chromatography. The serial purification method gave 2.80 fold of purification with a recovery of 17.38%. ChE was successfully purified in protein analysis through non-denaturing polyacrylamide gel electrophoresis (native-PAGE) and it proved that DEAE-cellulose matrix can serve as an effective medium to separate protein molecules. The optimum conditions for ChE assay was found to be at pH 9 in Tris-HCl and temperature of 35°C. Substrate specificity profile showed acetylcholinesterase (AChE) as the predominant enzyme which resides in partially purified samples because it indicated the highest Vmax and lowest Km when using acetylthiocholine iodide (ATC) as substrate. Inhibition study showed mercury as a strong inhibitor because it gave the highest percentage of inhibition effect (68.1%) towards ChE. Secondary screening found that half maximal inhibitory concentration (IC50) value for mercury was 1.8 mg/L. These finding suggested that partially purified ChE from brain extract of A. testudineus is suitable to be applied as biosensor to detect the presence of heavy metal in the environment.